IDENTIFIKASI PUSAT PERTUMBUHAN DAN INTERAKSI SPASIAL DI PROVINSI LAMPUNG - Emalia, Zulfa; Farida, Isti (Jurnal Ekonomi & Studi Pembangunan, 2018)
The aim of this research is to know the fast developed and growing area in Province Lampung, growth of pole area and the highest spasial interactions relationship between growth of pole area and hinterland area. This study uses secondary data taken from the site of the centre statistics agency and others linked. This analysis tool used are klassen typology, scalogram,Â  centrality index, ordinal scale, arcGIS and gravity index. The results showed that there are three areas in Province Lampung that is fast developed and growing is Bandar Lampung, Center Lampung and South Lampung. Bandar Lampung, Center Lampung and South Lampung became the growth of pole area in Province Lampung with the hinterland which have the highest interaction is Pesawaran East Lampung and Bandar Lampung City